Climate Factors Contribute to Irritant Contact Dermatitis Among Farmers: A Study in East Java, Indonesia - Kurnia Ardiansyah Akbar; Rosa Kumala Fatma; Syarifah Aqilah (The Indonesian Journal of Occupational Safety and Health, 2025)
Introduction: Irritant contact dermatitis is a common occupational disease among farmers, often triggered by environmental stressors. In Indonesia, particularly in Jember and Wuluhan District, over 70% of the population is engaged in farming, increasing vulnerability to climate-related health issues. This study aimed to examine the association between climate variables and the incidence of irritant contact dermatitis among farmers in Wuluhan District, East Java. Methods: A retrospective study was conducted using outpatient records from Lojejer Primary Healthcare Facility from July 2022 to December 2024. Included cases were farmers aged ≥17 years diagnosed with irritant contact dermatitis. Climate data—temperature, humidity, and wind flow—were obtained from the World Weather Satellite. Multiple linear regression assessed the relationship between monthly dermatitis cases and climate variables. Significance was set at p < 0.05. Results: A total of 462 dermatitis cases were recorded. Humidity was significantly associated with increased dermatitis incidence (p = 0.047; 95% CI: 1.464 to 0.011; R² = 0.369), suggesting a moderate predictive value. In contrast, temperature (p = 0.274) and wind flow (p = 0.624) were not significant. Conclusions: Humidity significantly contributes to irritant contact dermatitis among farmers, likely due to prolonged skin exposure and barrier dysfunction. These findings underscore the need for climate-responsive occupational health strategies, such as improved protective equipment and work schedule adaptations, to safeguard farmer health amid changing environmental conditions.